2008
DOI: 10.1177/1045389x08101565
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Finite Element—Circuit Simulation Model for Analyzing Piezoelectric Energy Generators

Abstract: A coupled finite element method (FEM) and circuit simulation approach for analyzing piezoelectric energy harvesters is presented. The advantage of the proposed method is that the mechanical analysis of the generator can be done using available FEM packages, while the circuit analysis can be performed using standard circuit simulation software (e.g., SPICE). The electromechanical coupling between the two physical domains is achieved by applying equivalent piezoelectric loads in the mechanical model, and equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
86
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 11 publications
1
86
0
Order By: Relevance
“…In most of the researches, the piezoelectric elements generate electricity using the movement of various things such as the human body [10][11][12][13] or wind [14,15]; however, these systems are not yet practical to use. In addition, the fundamental analysis [16][17][18] and design [5,[19][20][21] of vibration energy harvesting has also been studied intensively, as well as the circuit modeling of vibration energy generation based on the piezoelectric elements [22][23][24][25]. These two main factors are directly related to the efficiency of the electricity generated from the piezoelectric elements.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the researches, the piezoelectric elements generate electricity using the movement of various things such as the human body [10][11][12][13] or wind [14,15]; however, these systems are not yet practical to use. In addition, the fundamental analysis [16][17][18] and design [5,[19][20][21] of vibration energy harvesting has also been studied intensively, as well as the circuit modeling of vibration energy generation based on the piezoelectric elements [22][23][24][25]. These two main factors are directly related to the efficiency of the electricity generated from the piezoelectric elements.…”
Section: Introductionmentioning
confidence: 99%
“…In the power harvesting research area, novel technical concepts of the finite element methods have shown alternative solution techniques for investigating the self-powered MEMS devices using complex geometry of the laminated piezoelectric beams with electrode layers combined with the external circuit components. Only a few of the finite element selfpowered harvester research studies have been investigated by researchers during the last six years [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…FE models, on the other hand, are advantageous due to their versatility in modeling complicated geometry and its capability in obtaining full field solutions under any boundary conditions. In [19], FE methods are utilized for analyzing piezoelectric energy generators using different commercial software modeling multiphysics fields and the electric circuits, individually. Dedicate loops are designed in order to pass results between software.…”
Section: Introductionmentioning
confidence: 99%